(untitled) (British Journal of Global Ecology and Sustainable Development, 2024)
The medicinal properties of many plants are now being determined. One such peculiarity is the anti-inflammatory activity of natural compounds. Therefore, the anti-inflammatory failure of tetanus, incense, Parmesan, chamomile, common Ram, Rose and other plant extiracts was studied from local plants. The result was high anti-inflammatory activity with tetanus 96%, chamomile 83% and common Ram 87%. This article presents information about the cellular mechanism of inflammation and some medicinal plants.